Transformational leadership and project success: the serial meditating roles of team flexibility and team agility - Han, Huibin; Ma, Fangjing; Liu, Xinbo (Frontiers in Built Environment, 2024)
The construction sector is known for its dynamic nature, and numerous construction projects have failed to reach completion due to inadequate development of leadership. As a widely recognized leadership, transformational leadership has shown the positive relationship with project success. However, the mechanisms driving this relationship remain unclear in the context of construction projects. In response to this topic, by adopting the Input-Mediator-Outcome model, this study seeks to investigate the mediating effect of team flexibility and team agility between transformational leadership and project success in the context of construction projects. Data were collected through a survey from 306 construction project members. The Structural Equation Modeling method was employed to test the proposed model. The findings demonstrate that (1) transformational leadership positively impacts team flexibility and team agility; (2) team flexibility and team agility positively impact project success; (3) team flexibility shows a positive mediating effect between transformational leadership and project success; (4) team agility shows no mediating effect between transformational leadership and project success; and (5) team flexibility and team agility play serial mediating roles between transformational leadership and project success.